Diseño del plan de vigilancia de la salud en las empresas Wilpac Msi S.A. y Largenergy Cia. Ltda - Martínez Sarabia, Marcelo Javier (2022)
The objective of this research work was to design a health surveillance plan applicable to the companies WILPAC MSI S.A. and LARGENERGY Cía, according to their activity and line of business, referring to the study and medical assessment that should be performed to occupationally exposed workers, identifying that there was no health surveillance plan as such, adapted to the needs of the companies, obtaining through the research tools, the identification of common risks in both companies, and establishing a relationship that facilitates the implementation of measures within the health surveillance plan to prevent that these risks may affect the physical and mental health of workers, also using as a tool a check list of compliance with aspects of health surveillance, allowed to obtain a clear diagnosis of the current situation of the companies regarding six main aspects, health and safety management, the availability of health personnel and furniture necessary for the development of activities, the performance of occupational medical evaluations, immunization programs, epidemiological indicators and the application of specific prevention programs, making it possible to achieve a comparative vision of health surveillance between the two companies and to establish points for improvement, Similarly, with all the information gathered, the health surveillance plan is recommended, adapted to the needs of the companies, being applied appropriately in other types of projects that may arise, providing those responsible for safety and health at work, a valuable tool to be used for the benefit of the health of workers. KEY WORDS: Health, Surveillance, Prevention, Epidemiological indicators.